2021
DOI: 10.3390/biom11050613
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in Obesity and after Bariatric Surgery

Abstract: Iron deficiency (ID) is particularly frequent in obese patients due to increased circulating levels of acute-phase reactant hepcidin and adiposity-associated inflammation. Inflammation in obese subjects is closely related to ID. It induces reduced iron absorption correlated to the inhibition of duodenal ferroportin expression, parallel to the increased concentrations of hepcidin. Obese subjects often get decreased inflammatory response after bariatric surgery, accompanied by decreased serum hepcidin and theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 137 publications
0
14
0
3
Order By: Relevance
“…The effect of HIV-infection risk factors on adverse perinatal outcomes has not yet been disclosed. Risk factors such as poverty, lack of social support, anemia, diabetes, hypertension, chemo- or radiotherapy including different oncologic treatments [ 19 ], bariatric surgery involvement [ 20 ], or other pathogenic agents similar to hyper-virulent Klebsiella pneumoniae [ 21 ] could have important involvement on growth restriction, preterm birth, or even mortality of newborns [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of HIV-infection risk factors on adverse perinatal outcomes has not yet been disclosed. Risk factors such as poverty, lack of social support, anemia, diabetes, hypertension, chemo- or radiotherapy including different oncologic treatments [ 19 ], bariatric surgery involvement [ 20 ], or other pathogenic agents similar to hyper-virulent Klebsiella pneumoniae [ 21 ] could have important involvement on growth restriction, preterm birth, or even mortality of newborns [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis indicated that elevated serum ferritin was a risk factors for type 2 diabetes, and soluble transferrin receptor-to-ferritin ratio was inversely related to the risk of type 2 diabetes [ ( Liu et al, 2020b )]. Moreover, iron deficiency (ID) is particularly frequent in obese patients due to increased circulating levels of acute-phase reactant hepcidin and adiposity-associated inflammation which reduced iron absorption [ ( Bjørklund et al, 2021 )]. Jordi et al uncovered microbiome- and iron-linked metabolomic and transcriptomic signatures involving imbalances in gluconeogenic metabolites, ketone bodies and cellular transport, which altogether modulate liver fat accumulation [( Mayneris-Perxachs et al, 2021 )].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, intake of iron rich food is dramatically decreased in the first months after BS because of a general low food intake and poor tolerance of iron rich foods. On the other hand, RYGB and SG can induce malabsorption due to the decrease in the absorbing surface and the decrease of hydrochloric acid secretion due to the resection of the greater curvature of the stomach [41]. Furthermore, iron absorption may be compromised by other micronutrient supplements like calcium, thereby requiring a separate intake [33].…”
Section: Micronutrients Deficienciesmentioning
confidence: 99%